Research of modelling and nonlinear dynamic analysis for drive system of wind turbine generator. (2012) - Meng, Zong; Fu, Li-yuan; Song, Ming-hou
Using the Lagrange principle, the nonlinear dynamical equation of wind turbine generator drive system is presented, which considers nonlinear stiffness of the drive system. The stability of autonomous system is analysed by the Jacobian matrix. The stability of wind turbine generator drive system is analysed by using bifurcation and chaos theories. Finally, a numerical method is employed to describe the process of chaotic motion that the wind turbine generator drive system enters into chaos motion via period-doubling bifurcation by time domain waveform, phase trajectory and Poincaré map, and to analyse the effects of nonlinear factors on the stability of the system by bifurcation diagram.